Examining the impact of brand tribes relatives to brand loyalty and consumer relationships concerning the Iphone. - Munien, Charne' (The IIE, 2016)
This research study involves examining the impact of brand tribes relative to brand loyalty and consumer relationships concerning the iPhone. As such the branding techniques that influence brand loyalty, competitive advantage and the role these elements play in the facilitation of brand tribes have been explored. Furthermore this study explores the role this plays in driving purchase decisions among the youth market in the LSM categories 7-10 within South Africa. The study further aimed to ascertain the extent to which the iPhone brand has a communal following and whether this contributes to the success of the brand. The outcome of this study is a strategic model that facilitates and measures the success of the formation of brand tribes. The study took the form of an interpretive case study in which a mixedmethod research approach was employed. Qualitative and quantitative data were collected through online questionnaires with Apple iPhone consumers and interviews with Apple employees. The literature review also informed a large aspect of the study. The purpose of this study was to understand the inner workings of brand tribes, using Apple, a successful brand with a communal following as a case study. From the research findings, the most significant insights included the notion that brand tribes are built on the foundations of brand’s mirroring the behaviour of friendship through creating sincere emotional connections, positive brand experiences and connectivity. Overall it was found that the formation of brand tribes is highly beneficial to the success of the brand and this study poses a strategy to build brand tribes that contribute significant value to the lives of consumers as well as brands.
Theses
Keywords: Brand tribes; Brand loyalty; Consumer relationships concerning the iphone; Youth market (LSM categories 7-10); within South Africa